Information assurance dependability and security in networked systems - Qian, Yi, 1962- (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2008)
In todays fast paced, infocentric environment, professionals increasingly rely on networked information technology to do business. Unfortunately, with the advent of such technology came new and complex problems that continue to threaten the availability, integrity, and confidentiality of our electronic information. It is therefore absolutely imperative to take measures to protect and defend information systems by ensuring their security and non-repudiation. Information Assurance skillfully addresses this issue by detailing the sufficient capacity networked systems need to operate while under attack, and itemizing failsafe design features such as alarms, restoration protocols, and management configurations to detect problems and automatically diagnose and respond. Moreover, this volume is unique in providing comprehensive coverage of both state-of-the-art survivability and security techniques, and the manner in which these two components interact to build robust Information Assurance (IA). KEY FEATURES * The first and (so far) only book to combine coverage of both security AND survivability in a networked information technology setting * Leading industry and academic researchers provide state-of-the-art survivability and security techniques and explain how these components interact in providing information assurance * Additional focus on security and survivability issues in wireless networks.
PART I: SECURITY TECHNIQUES-- Security Services for Networks and Systems; Prevention and Protection I: Cryptographic Techniques; Prevention and Protection II: Cryptographic Protocols; Prevention and Protection III: Perimeter and System Security; Detection, Response and Assessment; PART II: SURVIVABILITY TECHNIQUES-- Availability and Survivability; Network Survivability; Survivability and Network Management; End System and Application Survivability; PART III: INTERACTION BETWEEN SECURITY AND SURVIVABILITY-- Models and Techniques for Secure and Survivable Systems; Design and Architectural Issues for Secure and Survivable Systems; Security and Survivability of Emerging Systems.
Includes bibliographical references and index.
Keywords: Computer networks -- Security measures; Computer networks -- Reliability; Computer security; Electronic books